THE ANALYSIS OF INDIRECT SPEECH ACTS IN THE MOVIE “SHERLOCK: THE EMPTY HEARSE” - Dita Nuraini Tiara; Eusabinus Bunau; Luwandi Suhartono (Universitas Tanjungpura, 2021)
AbstractThis research aimed to identify the indirect speech act and the intended meaning of the utterances in the movie Sherlock: The Empty Hearse. The data were taken directly from the movie dialogue, focusing on the indirect speech acts uttered by the characters, and the context of the occurrence of the utterance. The collected data were transferred to a table, which were analyzed using descriptive qualitative method. The data collection and analysis resulted in the findings of 11 data of indirect speech acts. The characters in the movie used indirect speech acts as request, command, suggestion, invitation, and refusal. Based on the findings, there were five data belonged to refusal speech acts, two requestspeech acts, one invitation speech act, two command speech acts, and one suggestion speech act. This showed that indirect speech act utterances in the movie were mainly used by the characters as a refusal to an offer or invitation.Keywords: Indirect Speech Acts, Movie, Speaker’s Intention, Speech Acts